Mineração e controvérsias sociocientíficas de forte impacto local na formação continuada de professores - Daniela Campolina Vieira (2021)
Minas Gerais, since its formation history, has mining as a reference economic activity. This is commonly seen, to this day, as a benefit to the state and the population. But this does not exempt the mining activity from several controversies, especially in relation to its local socioeconomic impacts. Some of these have been made visible after the last major disasters-crimes-collapse of dams that occurred in the state (Samarco-Vale-BHP in 2015 and Vale S.A. in 2019) that are configured in processes of technological disasters, triggered, therefore, from human failures. Problematized educational practices are increasingly necessary in view of the risks and uncertainties that permeate territories affected by mining and its dams. Especially when all the efforts of companies to develop socio-environmental marketing actions and stakeholder engagement with schools and communities in processes of territorial alienation and purposeful misinformation are added. In this context, we developed, under the CTSA bias, a new concept of didactic approach, Socio-Scientific Controversies of Strong Local Impact (SCSLI) based on three theoretical axes: territoriality of controversies, territorial-citizen awareness and environmental conflicts. The methodology of the thesis was organized in two guidelines. The first used cartography as a research-intervention method to trace the process of gestation of the CoSFIL concept-approach. The second guideline included the analysis of data referring to two socio-scientific controversies: (un)sustainability of mining and (un)safety of tailings dams. These were approached from the perspective of territorial problematization, taking as an example the Iron Quadrangle-Aquifer of Minas Gerais. Two moments of continuing education were structured for data collection: one in the Specialization Course in Science Education (Faculty of Education) and another in the Professional Master's in Biology Teaching (Institute of Biological Sciences), both at UFMG. In these formative moments, methodologies were also developed for the identification and territorial problematization of controversies. Among them the analysis of territoriality of disasters and the Geoparticipatory Mapping of Dams. We believe that the conceptual constructions arising from the thesis, the central one being the SCSLI concept-approach, can contribute both to the field of science teaching and to geographic and popular education, considering the importance of problematization in processes of formation of territorial awareness. -citizen in contexts of conflicts and environmental injustices, as well as risks of technological disasters.